2018
DOI: 10.1161/circulationaha.117.029901
|View full text |Cite|
|
Sign up to set email alerts
|

D-Dimer Predicts Long-Term Cause-Specific Mortality, Cardiovascular Events, and Cancer in Patients With Stable Coronary Heart Disease

Abstract: D-dimer levels predict long-term risk of arterial and venous events, CVD mortality, and non-CVD noncancer mortality independent of other risk factors. D-dimer is also a significant predictor of cancer incidence and mortality. These results support an association of D-dimer with fatal events across multiple diseases and demonstrate that this link extends beyond 10 years' follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 59 publications
7
102
0
4
Order By: Relevance
“…D‐dimer plays an important role in VTE exclusion, acute aortic dissection, DIC diagnosis, and other clinical settings, which has been well reviewed previously . Furthermore, because of the close relationship between coagulation, inflammation, and endothelial injury, elevation of D‐dimer level is also observed in patients with infection, surgery or trauma, malignance, and other nonthrombotic diseases …”
Section: D‐dimer Measurement and Its Traditional Applicationmentioning
confidence: 96%
See 1 more Smart Citation
“…D‐dimer plays an important role in VTE exclusion, acute aortic dissection, DIC diagnosis, and other clinical settings, which has been well reviewed previously . Furthermore, because of the close relationship between coagulation, inflammation, and endothelial injury, elevation of D‐dimer level is also observed in patients with infection, surgery or trauma, malignance, and other nonthrombotic diseases …”
Section: D‐dimer Measurement and Its Traditional Applicationmentioning
confidence: 96%
“…7-10 Furthermore, because of the close relationship between coagulation, inflammation, and endothelial injury, elevation of D-dimer level is also observed in patients with infection, surgery or trauma, malignance, and other nonthrombotic diseases. 7,[19][20][21][22]…”
mentioning
confidence: 99%
“…Circulating D‐dimer is also elevated in patients with liver disease, coronary artery disease and other cardiovascular diseases, cancer, trauma, pregnancy, infections, inflammatory diseases, severe renal disease, recent surgical procedures, and advanced age as summarized in Table . However, the D‐dimer elevation in these conditions is less specific than for DVT/PE.…”
Section: Common Uses Of D‐dimer Assaysmentioning
confidence: 99%
“…Despite this volume of data, its clinical value and significance for many indications remain controversial . Many attempts have been made to increase clinical utility of the D‐dimer test in a variety of other medical conditions, including combining D‐dimer with other laboratory tests and clinical algorithms …”
Section: Introductionmentioning
confidence: 99%
“…D-Dimer is a speci c degradation product under the action of plasmin after cross-linking of brin, and its increased level indicates that the body's secondary brinolytic activity is enhanced, re ecting the body's hypercoagulable and brinolytic state, and can be used for diagnosis Thromboembolic disease. And previous studies have shown that the elevation of D-Dimer is an important independent and persistent risk factor for cardiovascular events and cancer events [17] , as well as an early sign of impending MAS in febrile patients with active rheumatism and monitoring indicator for severe infections [18][19] . In this study, a ROC curve was used to analyze the diagnostic e ciency of various markers for EBV-HLH.…”
Section: Resultsmentioning
confidence: 98%